DEVELOPING STUDENTS’ LINGUCULTURAL COMPETENCE THROUGH ENGLISH LANGUAGE TEACHING (International Conference on Education, Psychology and Humanities, 2026)
This thesis examines the development of students’ lingucultural competence through English language teaching. Lingucultural competence is understood as the ability to use a foreign language with awareness of cultural meanings, national values, communicative norms, traditions and social behavior. The purpose of the study is to determine how English lessons can support not only linguistic knowledge, but also intercultural understanding. The study is based on theoretical analysis of pedagogical and linguistic sources. The findings show that the integration of authentic materials, cultural context, dialogue-based tasks and comparative analysis develops students’ ability to communicate appropriately in English. The thesis concludes that lingucultural competence is an essential condition for effective foreign language learning.
Keywords: lingucultural competence, English language teaching, intercultural communication, cultural awareness, communicative competence, authentic materials.